The use of cement leftovers from the hollow of spun piles as an additive in self-compacting concrete - Adnan, Suraya Hani; Adnan, Suzana Wati; Zakaria, Muhammad Shukri; Osman, Mohamad Hairi; Jamellodin, Zalipah (Construction Research Institute of Malaysia (CREAM), 2018)
Spun piles have been used widely by developing countries, including Malaysia, to construct the foundation of most construction projects. A spun pile is a reinforced precast and prestressed concrete that is compacted in a mould through spinning compaction. The spinning compaction produces cement leftovers in the hollow part of spun piles that can be added to concrete mixtures as an additive. The cement leftovers of spun piles were used as an additive in cement in range of 0%, 10%, 20% and 30% (equal percentages). The resulting compressive strength after curing periods of 7 days and 28 days were presented to investigate the properties of self-compacting concrete containing cement leftovers from the spun piles. Other properties investigated include the physical properties of fresh concrete and water absorption. The results indicated that higher compressive strength and lower water absorption were achieved by the concrete samples containing cement leftovers compared to controlled concrete.